Feasibility of Bioelectrical Impedance Spectroscopy Measurement before and after Thoracentesis. (11th March 2015) - Zink, Matthias Daniel; Weyer, Sören; Pauly, Karolin; Napp, Andreas; Dreher, Michael; Leonhardt, Steffen; Marx, Nikolaus; Schauerte, Patrick; Mischke, Karl
Abstract : Background. Bioelectrical impedance spectroscopy is applied to measure changes in tissue composition. The aim of this study was to evaluate its feasibility in measuring the fluid shift after thoracentesis in patients with pleural effusion. Methods. 45 participants (21 with pleural effusion and 24 healthy subjects) were included. Bioelectrical impedance was analyzed for "Transthoracic, " "Foot to Foot, " "Foot to Hand, " and "Hand to Hand" vectors in low and high frequency domain before and after thoracentesis. Healthy subjects were measured at a single time point. Results. The mean volume of removed pleural effusion was 1169 ± 513  mL. The "Foot to Foot, " "Hand to Hand, " and "Foot to Hand" vector indicated a trend for increased bioelectrical impedance after thoracentesis. Values for the low frequency domain in the "Transthoracic" vector increased significantly (P < 0 . 001 ). A moderate correlation was observed between the amount of removed fluid and impedance change in the low frequency domain using the "Foot to Hand" vector (r = - 0.7 ). Conclusion. Bioelectrical impedance changes in correlation with the thoracic fluid level. It was feasible to monitor significant fluid shifts and loss after thoracentesis in the "Transthoracic" vector by means of bioelectrical impedance spectroscopy. The trial is registered with Registration Numbers IRB EK206/11 and NCT01778270 .